Mapping of city growth with socio-economic growth data - Lei, Wong Lei (2018)
Many cities in Asia have been going through rapid urbanisation in the last few decades and this urbanisation is expected to continue. This project aims to map out city growth to track changes in urban growth over time. Capital stocks of structural assets, obtained from the Penn World Table (PWT), is used as a measure of the monetary value of a city’s assets at different time stamps. This project adopts a downscaling approach to generate a gridded database of assets using a reference grid size of 1 km x 1 km. Capital stocks for structures is distributed spatially using three different socio-economic indicators, namely population, land cover and road density. As part of a dual project, the scope of this paper is limited to two cities, namely Guangzhou, China and Bangkok Metropolitan Area, Thailand, which are two highly urbanised cities in Asia. My project partner, Cassandra Mun, will cover two other cities, namely the Philippines and Indonesia, in her work. With our work, we hope to inform policy makers and urban planners on city growth patterns and a potential tool that can be employed in crafting better strategies.